Optical redox ratio differentiates early tissue transformations in DMBA-induced hamster oral carcinogenesis based on autofluorescence spectroscopy coupled with multivariate analysis. (14th October 2016) - Sethupathi, R; Gurushankar, K; Krishnakumar, N
Abstract: Fluorescence intensity measurements have the potential to facilitate the diagnoses of many pathological conditions. The changes in fluorescence intensity may be influenced by factors such as tissue architectures, endogenous fluorophores, cellular metabolism and light penetration depth in tissue. Two of the most diagnostically important endogenous fluorophores are reduced nicotinamide dinucleotide (NADH) and flavin adenine dinucleotide (FAD), which can be used to monitor dramatic metabolic changes in cells and tissues. The goal of this study is to investigate changes in the endogenous fluorophore emission and to quantify metabolic changes in the redox state of various tissue transformation conditions with respect to control tissues in dimethyl benz[a] anthracene (DMBA)-induced hamster oral carcinogenesis for measuring emission spectrum at 320 nm excitation. In the present study, collagen, NADH and FAD emission of well-differentiated squamous cell carcinoma (WDSCC) showed decreased intensity at 385 nm, 450 nm and 520 nm compared to hyperplasia, dysplasia and control tissues. Furthermore, a significant decrease in the optical redox ratio is observed in WDSCC tissues, which indicates an increased metabolic activity compared to the control tissues. Moreover, the principal component linear discriminant analysis (PC-LDA) algorithm together with the leave-one-out cross-validation (LOOCV) method yield an overall diagnostic sensitivity of 77.7% and a specificity of 88.8% in the classification of control, hyperplasia, dysplasia and WDSCC tissues, respectively. The results from this study demonstrated that fluorescence-based tissue analysis combined with PC-LDA has tremendous potential for the effective discrimination of control from neoplastic tissues; furthermore it also detects early neoplastic changes prior to definite morphologic alteration.